DEVELOPMENT OF WARFARE AND COUNTER-TERRORISM: DEVELOPMENT OF WARFARE AND COUNTER-TERRORISM - Krastev, Kalin; Hristov, Hristo (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
In the XX-th and early XXI-st century оnе phenomenon has more acutely occurred in social and political life and although it has been going along with human development over centuries, today it contraries to the objective needs of the time, gets alarming proportions and becomes the primary global problem. This phenomenon is terrorism. It changes its forms аnd it is attaining more and more dangerous character for people through spreading to more countries; it is creating new threats to national security and political stability of countries and international relations. Today terrorism is a form of undeclared war against civilization and freedom of democratic societies and countries.